Effect of Reaction Time and Stability Properties of Gold Nanoparticles Synthesized by p-Aminobenzoic Acid and p-Aminosalicylic Acid - Abdul Aji; Sri Juari Santosa; Eko Sri Kunarti (Universitas Gadjah Mada, 2020)
In this work, we determined the influenced of the reaction time at the synthesis of gold nanoparticles (AuNPs) by p-aminosalicylic acid and p-aminobenzoic acid as reducing agent. Besides working as a reducing agent, the p-aminobenzoic acid and p-aminosalicylic acid also simultaneously played a role as a capping agent/stabilizing agent. Gold ion was first mixed with the pH adjusted p-aminobenzoic acid and p-aminosalicylic acid. The mixture then heated in boiling water at 86 °C. The formation of AuNPs was indicated by the appearance of red color and analyzed with UV/Vis spectrophotometry to evaluate their surface plasmon resonance (SPR) absorption in the wavelength range 400–800 nm. The reducing ability of the reducing agents was affected by its structure. Gold nanoparticles that were synthesized with p-aminosalicylic acid were more stable, faster and had a smaller size than its counterpart that is synthesized with p-aminobenzoic acid. The stability test over a periods 5 months showed that AuNPs were relatively stable.